Adverse Childhood Experiences and Criminal Motives: A Semantic Study of a Suicide Note - Theda Priskila Ann; Santoso, Bernadus Wahyudi Joko (JOLLT Journal of Languages and Language Teaching, 2026)
This research analyzes how traumatic childhood experiences shaped François Vérove’s criminal motives through a semantic study of his suicide note. This study fills the gap in the relationship between the impact of trauma and crime motive and legal framework through the assertions in suicide letters. Using a qualitative approach, the research analyzed a suicide note written by François Vérove, a former French gendarme. Linguistic analysis using Leech’s theory of meaning; psychological theory using adverse childhood experience by V.J. Felitti, and assisted by French laws—Code Pénal and Code de Procédure Pénale. Three stages of analysis were applied: trauma identification, meaning interpretation, and meaning relationship mapping. The findings show that word choice serves as a means of justification, emotional representation, and symbolic explanation for violent acts, while also indicating statements that violate French law. This study concludes that the application of linguistic analysis supported by psychological and legal perspectives can broaden our understanding of the perpetrator’s motives and determine the appropriate punishment for perpetrators who commit suicide.